In Pursuit of Legitimacy: The Muslim Brothers and Mubarak 1982-2000 by Hesham Al Awadi (New York: Tauris Academic Studies, 2004. 262 pages.) (American Journal of Islam and Society, 2006)
In his book In Pursuit of Legitimacy, Hesham Al Awadi sets out to explainEgyptian president Mubarak’s dramatic shift in his treatment of the MuslimBrothers (Al Ikhwan Al Muslimin), from toleration of the outlawed group tosevere repression, over the first two decades of his regime. Standard explanationsfor this shift, as Awadi points out, have a state-centric bias in which the state is the primary actor responding to the threat posed by the MuslimBrothers to the regime, either by providing social services when the state’scapacity to do so was hampered, or by challenging the legitimacy of anauthoritarian regime. The author acknowledges these factors, but then offersa substantially different narrative in which he skillfully traces the politicaldance of power between the outlawed group and the regime. The move torepression, in Awadi’s rendering, can be better explained by the responsiverelationship between the Muslim Brothers and Mubarak than by understandingeither power or legitimacy solely in terms of the state.Awadi argues that the driving force behind Mubarak’s crackdown inthe mid-1990s was a cyclical competition between the president and theMuslim Brothers for political legitimacy, which began with his regime’saccession following Sadat’s assassination in 1980. In his analysis, theauthor states that this conflict’s brutal 1995 climax, during which a numberof Muslim Brothers were convicted at a military trial, was by no meansa foregone conclusion. Rather, it was the result of a highly responsive relationshipbetween the regime and the increasingly powerful oppositionorganization. Moreover, it could have evolved differently had the MuslimBrothers made different choices about how to best pursue their program ...